An analysis on the triadic connection between seaports, inland terminals and hinterland market. Issue 1 (2nd January 2021) - Jeevan, J.; Othman, M. R.; Salleh, N. H. M.; Ghani, N. M. A.; Noralam, N. A.; Divine Caesar, Livingstone
ABSTRACT: Malaysian seaports face challenges of capacity utilisation due to unbalanced regional economic development. Additionally, the resulting challenge from mega shipping alliances may have effects on Malaysian seaports' competitiveness in the Southeast Asia region. To improve the existing space capacity, infrastructure and connectivity, seaports have moved forward by developing collaborative networks with other seaports in the same region or beyond the region to facilitate and boost trade without massive investments. Given the fact that Malaysian seaports are adopting co-operative strategies and there is limited academic research in seaport co-operation in the Malaysian context, this paper examines the forms of Malaysian seaport co-operation. It investigates factors driving co-operation in new and existing seaports. This paper firstly reviews relevant literature in order to classify the forms of seaport co-operation in Malaysia. Furthermore, the authors conduct a questionnaire survey of key seaport stakeholders (seaport organisations, shipping lines, shippers, inland port operators and port authorities and government officials) to investigate forms of, and the driving factors for, seaport co-operation. The findings provide an insight into seaport managers and government officials for decision-making related to strategies for seaport co-operation.